Polarised interleukin 8 secretion by HT 29/19A cells. Issue 3 (March 1994) - Lammers, K M; Jansen, J; Bijlsma, P B; Ceska, M; Tytgat, G N; Laboisse, C L; van Deventer, S J
Abstract : Interleukin 8 is a neutrophil chemotactic and stimulating cytokine induced by various inflammatory stimuli, including tumour necrosis factor, interleukin 1, and endotoxin. The ability of HT 29/19A enterocytes to synthesise interleukin 8 was studied. The results show that interleukin 1 is an important stimulus for interleukin 8 synthesis and secretion by HT 29/19A cells, being more potent than tumour necrosis factor. The tumour necrosis factor and interleukin 1 induced interleukin 8 secretion by HT 29/19A cells was seen to be polarised according to the direction of stimulation. These results support the concept that mucosal cells (enterocytes) may play an important part in initiating mucosal inflammation. Furthermore, it is proposed that HT 29/19A cells constitute a tool to study stimulus directed polarised cytokine secretion.